Association between maternal depression and neonatal outcomes: Evidence from a survey of nationally representative longitudinal studies - Li, Haoran; Ning, Wei; Zhang, Ning; Zhang, Jingya; He, Rongxin; Mao, Ying; Zhu, Bin (Frontiers in Public Health, 2022)
Background and aims Maternal depression before and after delivery has dramatically increased in China. Therefore, this study aimed to examine the association between antepartum and postpartum depression and neonatal outcomes. Design A population-based retrospective cohort study. Setting China. Participants Data were obtained from China Family Panel Studies (CFPS). Different mother-child/infant samples were included in this study. Mother in CFPS2012 and CFPS2016 were linked with 1–2-year-old children in CFPS2014 and CFPS2018, respectively. Besides, and mothers in CFPS2012, CFPS2016, and CFPS2018 were linked with 0–1-year-old infants in CFPS2012, CFPS2016, and CFPS2018, respectively. Methods Maternal depression was measured using the Center for Epidemiologic Studies Depression Scale. The neonatal outcomes included duration of gestational days, preterm birth, birth weight, birth weight z-score, weight, weight z-score, illness in the past month, and hospitalization in the past year. Propensity score matching was used to balance maternal, family, and infant/child characteristics between the maternal depression and non-maternal depression groups. Results Multivariable regression analysis of matched samples estimated that antepartum depression was associated with a shorter duration of gestation by 3.99 days (95% confidence interval [CI] = −7.21, −0.78). The association between antepartum depression and preterm birth, birth weight and birth weight z-score were not statistically significant. Postpartum depression was associated with more episodes of illness in the last month by 0.23 times (95% CI = 0.11, 0.36) and a higher odd of hospitalization in the previous year (OR = 1.59, 95% CI = 1.15, 2.20). The association between postpartum depression and weight or the weight z-score was not significant. Conclusion Maternal depression appears to be associated with worse neonatal outcomes.